Governança em cadeias globais de valor : um estudo entre agentes da cadeira de cafés especiais no Brasil e na Europa - Guimarães, Amanda Ferreira (2021)
The insertion of small rural producers in global value chains is an alternative for their permanence in activities. The sustainability of these chains depends on how they are organized, in terms of governance, especially when considering the transmission of information. Global value chains involve the transaction of a product or service that have some degree of differentiation, and different institutional environments and standards. Differentiation efforts may lead to transactions with greater asset specificity, dimensions that are difficult or costly to measure, and may lead to information asymmetry problems. Differences in transactions need distribution and remuneration of value, different transaction governance mechanisms and different chain governance mechanisms. Even then, there is a theoretical and empirical gap when considering these two governance mechanisms for efficiency in the creation, distribution, and remuneration of value in global value chains, especially in the case of the specialty coffee chain. Especially in the State of Paraná, in Brazil, the insertion of producers in markets aimed at differentiation constitutes an alternative for their survival in the activity. European Union countries such as Belgium, Holland and Sweden stand out in the import of specialty coffees from Brazil. Therefore, the goal of this study is to understand how the governance of the global value chain of specialty coffees (it's creation, distribution and remuneration of value) between agents in Brazil and European countries, is related to the governance of transactions throughout the chain. It is proposed the thesis that "the different characteristics of transactions along a chain in terms of their attributes, the measurability of the dimensions involved in the transaction and information asymmetry between agents, imply different governance mechanisms that, in a way, together, they will define the governance of the chain". Four theoretical strands were taken in account, complementary to each other, for this to be achieved. The Transaction Cost Economics, the Measurement Cost Economics, the Agency Theory and the Global Value Chain perspective. This qualitative and descriptive research was carried out through semi-structured interviews with 26 members of the CGV of specialty coffees involving the State of Paraná (Brazil) and four European countries (Belgium, France, The Netherlands, and Sweden) and three key agents in addition to non-participant observation in activities related to the purchase and sale of specialty coffees. As a result, it was observed that the GVC of specialty coffees under study is complex, heterogeneous, and non-linear, being in one hand producer-driven and, on the other hand, buyer-driven. In the studied global value chains, a set of value attributes was identified at the expense of the "coffee" asset itself, and from these attributes, two types of coffee were identified: standardized coffees and seasonal coffees. From this set of attributes, different levels of information complexity in the chain were identified, which imply different characteristics of the transactions and, consequently, different levels of integration downstream in the chain. It was found that the creation of value in this chain depends on the set of attributes transacted and it is predominant at different stages in the chain. In what comes to chain governance, this study shows that this chain cannot be vertically integrated, and may be governed by more than one leading company, implying co-governance between them. Finally, the characteristics of the chain and the transactions resulted in two modalities of chain governance: modular governance, and co-governance. It was observed that in the modular chain, uncertainty and asset specificity are concentrated in greater intensity in transactions involving intermediary agents in the chain (exporter, importer, and roaster), since they are responsible for guaranteeing the supply and construction of blends. In the co-governance chain, asset specificity and uncertainty are present upstream in the chain, since value creation is concentrated in transactions involving rural production. These results showed that the set of value attributes of the coffee to be produced created different characteristics of the set of 13 transactions that make up the chain, which demanded, in turn, distinct chain governance mechanisms. Compared to the modular chain, which involves codification of information, it was identified that the seasonal coffee chain depends on co-governance between the two leading companies, so that the information on the value created upstream associated with the extrinsic attributes is distributed further downstream. Finally, it was observed that the imbalances in coffee measurement identified in this study consist of governance failures that can compromise the distribution, remuneration, and support of the value created in the GVC of specialty coffees between the State of Paraná, Brazil, and European countries. Therefore, it was identified that there is a direct relation between transaction governance and chain governance.